Rational medication management mode and its implementation effect for the elderly with multimorbidity: A prospective cohort study in China - Tang, Qi; Wan, Litao; Lu, Jing; Wu, Wenhui; Wu, Huanyun; Liu, Zhenwei; Zhao, Sitang; Li, Chengyue; Chen, Gang; Lu, Jun (Frontiers in Public Health, 2022)
Background: As one of the countries with the most serious degree of aging, the incidence of potentially inappropriate drug use among the elderly is as high as 30.4% in Chinese communities, and the lack of effective medication management and poor medication compliance at home are the main factors. Given these situations, we constructed a Rational Medication Management Mode based on family physician service, carried out an empirical research and evaluated the implementation effect. Methods: A prospective cohort study was conducted from September to December 2021 to analyze the implementation effect of the Rational Medication Management Mode by comparing the outcome indicators between the intervention group and control group. The primary outcome of this study was medication number and polypharmacy (taking 5 or more medications) at 90 days. The secondary outcomes included the situation for behavioral self-management and knowledge-belief-behavior of rational medication use. Results: A total of 618 elderly patients (309 in the intervention group and 309 in the control group) with multimorbidity were included in this study, those were all available at follow-up at 90 days. At 90 days, the number of medications was achieved by 3.88 (1.48), and patients with polypharmacy were reduced by 59.55% in the intervention group, having a significant difference compared with the control group (P < 0.001). Patients with medication reminders, intermittent medication and adverse drug reactions were achieved in 294 (95.15%), 47 (15.21%), and 51 (16.51%) respectively in the intervention group (P < 0.001). The knowledge, belief, behavior security and behavior compliance of rational medication use of elderly patients were all greatly improved in the intervention group at 90 days (P < 0.0001). Conclusion: The Rational Medication Management Mode based family physician service, which provides the support of manuals and pillboxes, can decrease the elderly patients’ number of drugs with multimorbidity, reduce the incidence of polypharmacy, enhance behavioral self-management, increase the knowledge and belief of rational medication use, and improve the security and compliance of medication usage behavior. In order to provide a practical basis for rational medication management of elderly patients with multimorbidity under the background of long-term prescriptions in China.